1988
DOI: 10.1111/j.1365-2621.1988.tb09294.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Adzuki Bean (Vigna angularis cv Takara) Proteins

Abstract: Protein extract (P-I), isolate (P-II), albumin (PA), and globulin (PC?) were isolated from Minnesota-grown adzuki beans. Total extractable protein and water-and salt-soluble fractions accounted for 21.6, 15.8, and 2.3% (d.b.), respectively. Fractions were compared with a commercial soy protein (PS) for chemical and functional properties. Proteins in P-I, PA, PG, P-II, and PS wcrc 78.8, 69.4, 89.2, 91.3, and 89.9% (d.b.), respectively. P-I, PA, and PG wcrc superior to PS in essential amino acid contents; P-II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 37 publications
5
35
0
Order By: Relevance
“…On the other hand, the high concentration of glutamic and aspartic acids were found in the globulin fraction. 42,43 The concentrations of albumin, globulin, prolamin, and glutelin, for the control and enriched (3000 µg Fe III -EDTA) groups are presented in Table 6. Solubility of a protein depends on amino acid composition and results from thermodynamic equilibrium between the protein-protein interaction and the protein-solvent interaction; the solubility is related to the hydrophilicity-hydrophobicity balance.…”
Section: Effects Of Enrichment On the Distribution Of Proteins And Fementioning
confidence: 99%
“…On the other hand, the high concentration of glutamic and aspartic acids were found in the globulin fraction. 42,43 The concentrations of albumin, globulin, prolamin, and glutelin, for the control and enriched (3000 µg Fe III -EDTA) groups are presented in Table 6. Solubility of a protein depends on amino acid composition and results from thermodynamic equilibrium between the protein-protein interaction and the protein-solvent interaction; the solubility is related to the hydrophilicity-hydrophobicity balance.…”
Section: Effects Of Enrichment On the Distribution Of Proteins And Fementioning
confidence: 99%
“…Legume lipids and dietary fibers are being suggested for dietary reduction of blood cholesterol because legumes contain substantial amounts of desirable polyunsaturated fatty acids (PUFA) and fiber [10]. The nutritive value of adzuki beans has been investigated in studies concerned with the chemical composition of the whole seed reported by Hayakawa and Breene [11], Tjahjadi et al [4], Hsieh, Pomeranz and Swanson [12]. Knowledge of TAG structure has also become increasingly important since the stereospecific structure influences the lipid metabolism [13] and bioavailability of FA.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant use of adzuki in traditional Japanese confections is a paste or wagashi such as youkan, manju and amanatto [1][2][3]. Adzuki beans are a rich source of carbohydrates, protein, vitamins, minerals and fiber [4]; however, they also contain antinutritional factors. Phytates, α-galactosides and trypsin inhibitors are among these factors, and their concentrations differ widely among the different cultivars of adzuki beans.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates are the major compound in adzuki beans, which also contains fiber, protein, vitamins, and minerals (Tjahjadi et al, 1988). In Asia, boiled adzuki bean juice has been used as a folk remedy to prevent damage associated with aging (Maruyama et al, 2008).…”
mentioning
confidence: 99%